Federalism and decentralization: a critical survey of frequently used indicators - Lorenz Blume; Stefan Voigt (Philipps-University Marburg, Faculty of Business Administration and Economics, 2008)
The economic effects of federalism are unclear: some papers find that federalism has strong positive effects on a number of economically relevant variables, others find negative effects. The results often crucially hinge upon the proxies for federalism used. In this paper, we critically survey the existing indicators for both federalism and fiscal decentralization. We argue that federalism is a constitutional institution whereas decentralization is (the outcome of) a policy choice and that the two ought to be systematically distinguished because decentralization can also occur in non-federally structured states. We further argue that institutional details are very important with regard to federalism and that dummy variables usually capture only very specific aspects of the institutional details. We use factor analysis to test whether the latent variables behind the observed indicators support these assumptions. It is shown that more than two important factors result, implying that a more fine-grained differentiation beyond the distinction between federalism and decentralization might be in order. The correlations of the most important proxies for various aspects of federalism and decentralization with a number of (quasi-) exogenous variables as well as with institutional variables are usually rather modest.
Keywords: H1; H3; H5; H8; 330; Federalism; Fiscal federalism; Decentralization